Sports Utility Vehicles and vulnerable road users - O'NEILL, DESMOND; SIMMS, CIARAN KNUT (British Medical Journal, 2006)
Two independent trends in the developed world are likely to reverse some of the hard won improvements that have been made in road safety. One is the ageing of the population; the other the increase in the use of sports utility vehicles (SUVs, high performance four wheel drive cars capable of off-road driving). The first trend produces a growing number of vulnerable road users; the second produces a likelihood of more severe injuries when vehicles and pedestrians collide. Public health professionals will need to work with transportation and road safety agencies to avoid the inevitable consequences of more vulnerable road users and more lethal vehicles.
PUBLISHED
Keywords: Public and environmental health; sports utility vehicles